COST BENEFIT ANALYSIS OF COMPROMISING LEDGER SYSTEM BASED ON BLOCKCHAIN TECHNOLOGY - Edis Mekić; Safet Purković; Ahmedin Lekpek (BizInfo)
Modern application of the blockchain technology is the center of attention of technology and economy sectors. Proper usage of blockchain is based on peer to peer (P2P) network to coordinate a worldwide, universal ledger where all transactions on the network are recorded. In order to provide security and veracity of ledger system blockchain systems uses cryptographic hash function. By hashing the block sent by the member of P2P network and checking if it still fits the pattern for the next block, the network can easily prove that the calculating machine did in fact find coded solution of function. Before adding data received on this way majority of the machines on the network must provide consensual confirmation of transaction. this confirmation must be confirmed with at least 51% of machines in the system. This is first and most analyzed vulnerability of this type of ledger systems based on blockchain. In this research we analyzed cost benefit analysis for implementation of the proposed attack on three popular block chain systems, and proved that investment in equipment for conducting this type f attack is not beneficial for potential attacker.